Low-profile four-port MIMO antenna realizing penta-band notches for UWB systems - Al Gburi, Ahmed Jamal Abdullah; Saritha, Vanka; Venkata Naga, Koteswara Rao Devana; Lakshmi, Munagoti Bhagya; Halimi, Md Ahsan; G. S. K., Gayatri Devi; Lavuri, Nageswara Rao (Elsevier, 2025)
This paper presents a low-profile, four-port Ultra-Wideband (UWB) Multiple-Input MultipleOutput (MIMO) antenna with integrated penta-band notch functionality to suppress interference from coexisting narrowband systems. The antenna employs a combination of mushroom-type Electromagnetic Bandgap (EBG) structures and inverted L-shaped slots to realize five distinct notched bands at 3.5, 4.1, 5.0, 6.7, and 7.8 GHz, each exhibiting rejection levels better than − 4 dB. This effectively mitigates interference from WiMAX, INSAT, Wi-Fi (5 G), Wi-Fi-6E (6 G), and X-band uplink services. The four antenna elements are arranged face-to-face to minimize mutual coupling and ensure improved isolation. Notching is achieved using two square mushroom EBG structures, a spiral-slot EBG near the feedline, and three inverted L-shaped slots on the radiating surface. To enhance compactness further, a spiral-shaped defect is incorporated into one of the EBGs. Additionally, two square EBGs placed symmetrically beside the feedline enable the 5.5 GHz notch. The antenna occupies a compact footprint of 45.3 × 69.8 × 1.6 mm³ and demonstrates excellent diversity performance, with Envelope Correlation Coefficient (ECC) values below 0.02 and Diversity Gain (DG) near 10 dB. Performance validation includes frequency response, surface current analysis, ECC, DG, and radiation patterns, confirming the design’s suitability for compact UWB wireless devices requiring multi-band interference suppression.